2017
DOI: 10.1016/j.diagmicrobio.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli sequence type 73 as a cause of community acquired urinary tract infection in men and women in Rio de Janeiro, Brazil

Abstract: Escherichia coli clones ST131, ST69, ST95 and ST73 are frequent causes of urinary tract infections (UTI) and bloodstream infections. Specific clones and virulence profiles of E. coli causing UTI in men has been rarely described. The aim of this study was to characterize patient and clonal characteristics of community-acquired UTI caused by E. coli in men (n=12) and women (n=127) in Rio de Janeiro, Brazil, complementing a previous work. We characterized isolates in phylogenetic groups, ERIC2-PCR and PFGE types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
(44 reference statements)
3
6
0
1
Order By: Relevance
“…The traT gene was mostly detected among ST69 isolates. This finding has been reported in previous surveys 20. The traT protein is responsible for development of a resistance phenotype against serum bactericidal activity, and may confer additional advantage to ST69 isolates.…”
Section: Discussionsupporting
confidence: 87%
“…The traT gene was mostly detected among ST69 isolates. This finding has been reported in previous surveys 20. The traT protein is responsible for development of a resistance phenotype against serum bactericidal activity, and may confer additional advantage to ST69 isolates.…”
Section: Discussionsupporting
confidence: 87%
“…This study characterised the E. coli strains isolated from DFOM and deep DFI and demonstrated that these bacteria were highly genetically diverse with different pathogenicity traits. Among them, some strains belonged to ST73, a major clonal complex isolated from UTI particularly pyelonephritis and associated with multidrug resistance profile [35][36][37]. Moreover, these strains were isolated from monomicrobial infection in our panel confirming their virulence potential.…”
Section: Discussionsupporting
confidence: 53%
“…En 2017 Souza, et al reportaron una frecuencia del gen afa en aislamientos UPEC de 9 % (18) , pero no encontraron una asociación significativa entre el gen y el filogrupo, ni con el género del paciente de donde se aisló. Además, mostraron que la presencia del gen afa y la no sensibilidad a la amika-Figura 1.…”
Section: Discussionunclassified